The challenges of physicians' participation in hospital accreditation programs: a qualitative study in Iran - Hosein Ebrahimipour; Elahe Hooshmand; Mehdi Varmaghani; Javad Javan-Noughabi; Seyyed Morteza Mojtabaeian (BMC, 2021)
Abstract Background Due to the increasing pressure on hospitals to enhance the quality of services, the participation of physicians in accreditation programs has become more important than ever. The present study was conducted to describe challenges of physicians' participation in hospital accreditation programs in Iran using a qualitative approach. Methods We conducted interviews with 11 managers, 9 physicians and 8 experts in the field of hospital accreditation. Interviewees were selected through purposive snowball sampling. In-depth unstructured and semi-structured interviews were conducted for data collection. The data obtained were analyzed in ATLAS.ti using the conceptual framework method. Results The results of this study extracted 3 main themes including: cultural, organizational and behavioral factors. Also, this study found 12 sub-themes and 57 items. Sub-themes in the cultural domain were motivation, patient demand, mutual trust and evaluation system. The organizational domain consisted of seven sub-themes, including high workload, understanding the role of quality management unit, unrealistic accreditation, nature of accreditation, empowerment of physicians in the field of quality, effective communication, resource constraint. Sub-themes in the behavioral dimension were ambiguity in the role and uncertainty about how to participate in accreditation program. Conclusion Physicians' participation in accreditation programs can be increased through culture building and proper training about accreditation activities in the medical community.